2016
DOI: 10.5370/jeet.2016.11.5.1210
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Feasibility of a Foot Gear Type Energy Harvester Using a Textile Coil Inductor

Abstract: -This research developed a textile coil inductor, in which conductive yarn was wound spirally onto textile, and produced an energy harvesting module utilizing a cylindrical compression coil spring structure to allow a permanent magnet to spin in the center hole of the coil inductor. The study confirmed through a pilot test that the voltage increased as the number of laminated layers of the coil inductor increased. Five subjects were tested in the energy harvesting measuring experiment after producing a sports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Since harvester parts are not meant to be enclosed in any rigid housing, there is no need to allocate any space for magnet movement like it is in traditional cylindrical coil construction [14], flat coils with magnetic suspension [34], or with the magnet moving through the coil [20]. Power density is considerably higher than for other electromagnetic harvesters summarized in [1], but most of them rely on inertia and thus have resonant frequency, which is high (e.g., P/V = 2,2 mW/cm 3 at f = 320 Hz).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since harvester parts are not meant to be enclosed in any rigid housing, there is no need to allocate any space for magnet movement like it is in traditional cylindrical coil construction [14], flat coils with magnetic suspension [34], or with the magnet moving through the coil [20]. Power density is considerably higher than for other electromagnetic harvesters summarized in [1], but most of them rely on inertia and thus have resonant frequency, which is high (e.g., P/V = 2,2 mW/cm 3 at f = 320 Hz).…”
Section: Discussionmentioning
confidence: 99%
“…Authors and other researchers have previously shown that it is possible to use flat spiralshaped coils [19,20] as inductors in electrodynamic harvesters and elements of electronic circuits. Another advantage of electromagnetic harvesters is their ability to work without direct contact between harvester elements, as it is necessary, for example, with piezoelectric harvesters; therefore, it is possible to implement them without changing shape, elasticity, and other mechanical properties of clothing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic induction occurs when a conductive coil is placed within a varying magnetic field generating an electric current in the coil, and therefore this technique can be used to harvest energy from motion. Electromagnetic induction has been investigated for powering wearable devices [ 65 , 66 , 67 , 68 , 69 ], especially for shoes. An electromagnetic induction-based energy harvester normally has a permanent magnet at its core which is free to move inside of a tubular structure onto which conductive induction coils are mounted.…”
Section: Textile Energy Harvestingmentioning
confidence: 99%
“…Electromagnet systems have much higher efficiency in the mechanical-to-electrical energy transfer, while it usually involves coils and magnets (Cho et al, 2016;Ylli et al, 2015), which means a complicated and bulky mechanism is unavoidable. Piezoelectric materials can directly produce charge when stress is applied on it, and thus, piezoelectric energy harvesting (PEH) is widely studied (Xie and Cai, 2014) for some integrated working circumstances.…”
Section: Introductionmentioning
confidence: 99%